Estimates of cancer burden in Puglia. Issue 3 (May 2013) - Galise, Ida; Rashid, Ivan; Cuccaro, Francesco; Bisceglia, Lucia; Coviello, Vincenzo; Melcarne, Anna; Minerba, Sante; Mincuzzi, Antonia; Assennato, Giorgio; Foschi, Roberto; Rossi, Silvia; Gatta, Gemma
Aims and background: A regional population-based cancer registry that provides incidence and survival data has become active only recently. Since it is important to know the time trends of basic epidemiological indicators to understand the cancer burden in the region, this paper will provide incidence, prevalence and mortality estimates in the region for seven major cancers for the period 1970—2015. Methods: The estimates were obtained by applying the MIAMOD method, a statistical back-calculation approach to derive incidence and prevalence figures starting from mortality and relative survival data. Survival was modeled on the basis of published data from the Italian cancer registries. Results: The incidence rates are estimated to be still increasing for female breast cancer, colorectal cancer in men and skin melanoma in both sexes. By contrast, the incidence rates indicate a decreasing trend for cervix uteri cancer and stomach cancer, the latter both in men and women. For these cancers an analogous trend is observed for mortality, confirming the reduction of the risk factors related to these cancer types. The incidence rates for lung cancer and prostate cancer in men were estimated to rise, reach a peak, and then decrease in the last part of the considered period. Prevalence increased for all the considered cancers except cervix cancer. The increase was striking for breast cancer and less pronounced for stomach cancer in both genders. Conclusion: This paper provides a description of the burden of the major cancers until 2015. The results highlight the need to reinforce effective preventive measures to contrast cancers related to an unhealthy lifestyle and to increase the compliance with organized screening programs to reduce the colorectal and breast cancer burden.